Facile synthesis of new N-sulfonamidyl-4-thiazolidinone derivatives and their biological evaluation - Subhedar, Dnyaneshwar D.; Shaikh, Mubarak H.; Khan, Firoz A. Kalam; Sangshetti, Jaiprakash N.; Khedkar, Vijay M.; Shingate, Bapurao B. (New Journal of Chemistry, 2016)
The one-pot three-component syntheses of new N-sulfonamide-thiazolidin-4-one derivatives were carried out in excellent yield using [HDBU][HSO4] as an ionic liquid under solvent-free conditions. The newly synthesized compounds were screened against fungal strains and a number of compounds were seen to display excellent antifungal activity. In addition, the synthesized compounds were screened for their scavenging activity of the 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical and showed very good antioxidant activity. Finally, theoretical predictions derived from molecular docking studies against the potential target sterol 14 alpha-demethylase (CYP51) helped establish a link between the observed biological activity and the binding affinity, thereby providing insights into the specific bonding and non-bonding interactions governing the activity.

Facile and solvent-free domino synthesis of new quinolidinyl-2,4-thiazolidinones: antifungal activityand molecular docking - Subhedar, Dnyaneshwar D.; Shaikh, Mubarak H.; Tupe, Santosh G.; Deshpande, Mukund V.; Khedkar, Vijay M.; Jha, Prakash C.; Shingate, Bapurao B. (Mini-Reviews in Medicinal Chemistry, 2018)
Objective: We have synthesized new quinolidinyl-thiazolidinones via Knoevenagel condensation-alkylation reaction, catalyzed by [Et3NH][HSO4]. The present approach offers several advantages such as higher yields, eco-friendly reaction condition and economic availability of the catalyst. Method: The newly synthesized compounds were evaluated for their in vitro antifungal activity against six fungal strains. Some of the synthesized conjugates displayed good to moderate antifungal activity. Conclusion: Again, the molecular docking study performed against the fungal sterol 14 alpha-demethylase (CYP51) showed an excellent binding affinity towards the enzyme which could rationalize the promising antifungal activity portrayed by these derivatives and provides a platform for structure based drug design.